High temperature diffraction study of in-situ crystallization of nanostructured TiO2 photocatalysts - Low, It Meng; Curtain, Ben; Philipps, M.; Liu, Z.; Ionescu, M. (Australian Ceramic Society, 2012)
The in-situ crystallization of anatase and rutile on chemically-treated Ti-foils in the temperature range 20-900ºC has been investigated using synchrotron radiation diffraction and x-ray diffraction. The processing methodology has a profound influence on the morphology, crystallite size and growth rate of nanostructured TiO2. The anatase formed was metastable and transformed to rutile at ~800ºC. Increasing the temperature from 400 to 900ºC caused the sharpening of anatase (101) peaks and resulted in a concomitant coarsening in crystallite size. The surface of annealed samples exhibited TiO2 nanorods, nanowires or nanotubes depending on the processing method. Ion-beam analysis has indicated the existence of composition gradation within the annealed TiO2 samples at the near-surface.